Transformative Supervision and Teacher Agency: How Integrated Supervision Reshapes Teachers’ Professional Identity and Performance - Shofwani, Siti Aniqoh; Raharjo, Tri Joko; Fakruddin, Fakhruddin; Arief, Sandy; Taufikin, Taufikin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study explores the meaning of integrated supervision for teachers as a form of control or empowerment, and its impact on their agency and professional identity. Using a mixed methods design with a predominantly qualitative approach, the study was conducted in secondary schools in Indonesia. In the first phase, a survey of 80 teachers mapped their perceptions of supervision and their levels of agency. The next phase, in-depth interviews with 10 teachers, explored their experiences in supervisory practice. Findings indicate that control-based supervision tends to suppress teacher agency, shape a defensive professional identity, and reduce pedagogical initiative. Conversely, dialogic and trust-based supervision strengthens teacher agency, shapes a reflective professional identity, and encourages pedagogical courage. This study contributes in three aspects: first, it proposes the Transformative Supervision–Agency Loop model to explain the interaction of supervision, agency, and professional identity; second, the model builds on teachers’ narrative experiences; and third, it demonstrates the value of a mixed methods approach in capturing the relational and emotional dimensions of supervision. By shifting the analytical focus from managerial effectiveness to teacher subjectivity, this study offers a humanistic framework for reimagining supervisory practice in secondary education.